1993
DOI: 10.21273/jashs.118.5.593
|View full text |Cite
|
Sign up to set email alerts
|

Benzyladenine and Other Chemicals for Thinning `Empire' Apple Trees

Abstract: Postbloom applications of benzyladenine (BA) thinned young fruitlets of mature `Empire' apple trees (Malus domestica Borkh.) as well as or better than NAA or carbaryl (CB). BA increased fruit weight more effectively than either NAA or CB. Promalin (PR) was less effective than BA for both thinning and fruit-weight increase. In 1990, both BA and PR reduced fruit set up to 29 days after full bloom, but PR showed less thinning activity. BA and NAA produced independent and additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
4
30
2
1
Order By: Relevance
“…The results agree with those of Elfving and Cline [3,4] who reported that the application of ethephon and NAA had no effect on the apple tree fruit setting.…”
Section: Effect Of the Growth Regulators On The Fruit Setting Percentagesupporting
confidence: 92%
See 1 more Smart Citation
“…The results agree with those of Elfving and Cline [3,4] who reported that the application of ethephon and NAA had no effect on the apple tree fruit setting.…”
Section: Effect Of the Growth Regulators On The Fruit Setting Percentagesupporting
confidence: 92%
“…The past few years have witnessed significant advances in the use of synthetic and natural plant bioregulators for the improvement of crop performance in citrus [1,2], apple [2][3][4][5] and avocado [6]. Date palm trees (Phoenix dactylifera L.) are among the most cultivated horticultural crops in the United Arab Emirates.…”
Section: Introductionmentioning
confidence: 99%
“…Accel was usually applied to small fruit in the present study, and thinning results may have been improved if treatments were applied when fruit diameter averaged 10 to 12 mm. BA was most effective when applied at an average fruit diameter of ≈10 mm (Greene, 1993), but in another study it was effective when applied over a period of 29 d after bloom (Elfving and Cline, 1993). Easy-to-thin cultivars required BA concentrations of 50 to 75 mg·L -1 , and diffi cult-to-thin cultivars required 75 to 100 mg·L -1 .…”
Section: Discussionmentioning
confidence: 95%
“…A contrast between NAA + CB at PF and/or Accel ™ + CB at 10 mm KFD vs. the commercial standard showed greater cropload adjusted fruit weight than the commercial standard in 1996 (P = 0.0289) but the probability of difference was only 0.1952 in 1997. BA has been reported to enhance fruit growth beyond the direct affect of thinning (Elfving and Cline;1993;Greene et al, 1992), which has been attributed to increased cell division (Greene et al, 1990;Wismer et al, 1995). Robinson and Lakso (1991) found that early application of NAA suppressed fruit growth less than when applied at 10 mm KFD.…”
Section: Discussionmentioning
confidence: 99%